Comparison of Antioxidant Activity of Sheet Mask Ethanol Extract of Kesum Leaves (Polygonum Minus H) Using DPPH and FRAP Methods - Tiara Rizki Ambararum; Annie Rahmatillah; Vivin Marwiyati Rohmana (International Journal of Health Engineering and Technology, 2026)
Skin aging due to oxidative stress from free radicals requires natural antioxidants such as kesum leaves (Polygonum minus Huds.) which are rich in flavonoids and phenolics. This study aims to formulate a sheet mask from ethanol extract of kesum leaves at a concentration of 1-3%, evaluate the physicochemical properties, and compare antioxidant activity with DPPH and FRAP methods. Quantitative experimental research with a comparative design used purposive sampling of kesum extracts and formulations (F0-F3), with three replications per concentration (a total of 12 samples). Instruments include a UV-Vis spectrophotometer (DPPH 517 nm, FRAP 593 nm), pH meter, viscometer; linear regression data analysis for IC₅₀ and t/ANOVA test. The results showed that the IC₅₀ extract DPPH 38.12 ppm (very strong) and FRAP 67.37 ppm (strong); F3 sheet mask optimal IC₅₀ DPPH 41.59 ppm, pH 5.43, viscosity 385 mPa.s, spreadability 6.7 cm, non-irritant, increased humidity 50-60%. The DPPH method is more sensitive than FRAP. In conclusion, F3 sheet mask has the potential to be a strong antioxidant for anti-aging cosmetics, in vivo and stability tests are recommended.